计算3(a+b)-2(a-b)-a=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 11:52:53
计算3(a+b)-2(a-b)-a=计算3(a+b)-2(a-b)-a=计算3(a+b)-2(a-b)-a=答案是5b.
计算3(a+b)-2(a-b)-a=
计算3(a+b)-2(a-b)-a=
计算3(a+b)-2(a-b)-a=
答案是5b.
计算3(a+b)-2(a-b)-a=
计算:(a+b)(2a-3b)
计算(a-b)(b-a)^3+[(a-b)^2]^2
计算a/a+2b-b/3a-b
计算(5a-3b)^2+(a+b)(a-b)
计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=
计算a^2b^2+3a-3b=
计算(3a+2b)(3a-2b)=
计算:(4a-b)^2-[8a*(a-b)-(3a-b)*(3a+b)]
计算a+[a+b]+[a+2b]+[a+3b]+...+[a+99b]
计算:a+(a+b)+(a+2b)+(a+3b)+……+(a+99b)
计算a+(a-b)+(a-2b)+(a-3b)+.+(a+99b)
计算(a-2b)(-4a)=
a=2,b=-3,c=-1,计算:|a-b|+|b-c-a|.
a*b=4a-3b-a×b 计算2*(—3)
a*b=4a-3b-a×b 计算2*(—3)
已知a+b=-3,ab=2,计算根号b/a+根号a/b详解
已知a+b=-3,ab=2,计算根号b/a+根号a/b详解